Analysis of Futsal Shooting Skill Levels in the Extracurricular Program at SMPN 12 Kota Bengkulu - Prasetio Alfa Rido; Rafles Ramadan; Roberto Wilson; David Andriyan Dino; Edri Alfarizi; Supriyanto Supriyanto (Educative Sportive, 2025)
This study aims to analyze and describe the futsal shooting skill levels of students in the extracurricular program at SMPN 12 Bengkulu City. This was a descriptive quantitative study using a survey method. The population and sample consisted of all 30 active futsal extracurricular students, selected using total sampling. The research instrument utilized a futsal shooting skill test with 10 attempts (5 with the right foot and 5 with the left foot). The data were analyzed using descriptive percentage statistics. The results indicated that the majority of students' shooting skills fell into the "Medium" category at 40% (12 students). Meanwhile, the "Good" category was 23.3% (7 students), "Poor" was 20% (6 students), "Very Good" was 10% (3 students), and "Very Poor" was 6.7% (2 students). On average, the students achieved a score of 5.20 or 52%. The study concludes that the shooting skills of futsal extracurricular students at SMPN 12 Bengkulu City are at an intermediate level, with the main obstacles being the inefficiency of follow-through movements, body balance, and the disparity in non-dominant foot usage. Coaches are advised to optimize mechanical drill exercises and balanced usage of both feet to improve the accuracy and power of the students' shots.